2009
DOI: 10.1002/hlca.200800272
|View full text |Cite
|
Sign up to set email alerts
|

Sesquiterpenes and Lignans from Tephrosia vogelii

Abstract: A new guaiane sesquiterpene, (1b,6a,10a)-guai-4(15)-ene-6,7,10-triol (1), and a new lignan, (þ)-lariciresinol 9'-stearate (2), were isolated from the aerial parts of a leguminosae plant, Tephrosia vogelii, together with three known compounds, teclenone B, (1b,7R*)-opposit-4(15)-ene-1,7-diol, and pinoresinol. Their structures were elucidated on the basis of spectral data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…The configuration of C-10 is then determined by the NOESY correlations H-1/H-14 and H-6/H-14, and the lack of the correlations H-5/H-14 and H-7/H-14, suggested that methyl group (δ 29.7) at C-10 was α-oriented in equatorial position [16][17][18]. The downfield resonance (δ 2.62) of the H-5 proton, due to a cis spatial relationship with the OH-10, also supported this point [16].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The configuration of C-10 is then determined by the NOESY correlations H-1/H-14 and H-6/H-14, and the lack of the correlations H-5/H-14 and H-7/H-14, suggested that methyl group (δ 29.7) at C-10 was α-oriented in equatorial position [16][17][18]. The downfield resonance (δ 2.62) of the H-5 proton, due to a cis spatial relationship with the OH-10, also supported this point [16].…”
Section: Resultsmentioning
confidence: 99%
“…Kadsuguain A (1) was obtained as a colourless gum, whose molecular formula was determined to be C 15 , and between H-6 and H-7 (each 10.5 Hz) indicated that H-5 and H-7 were positioned at the same orientation (β-form) and H-1 and H-6 were then on the opposite side (α-form) [17]. The configuration of C-10 is then determined by the NOESY correlations H-1/H-14 and H-6/H-14, and the lack of the correlations H-5/H-14 and H-7/H-14, suggested that methyl group (δ 29.7) at C-10 was α-oriented in equatorial position [16][17][18].…”
Section: Resultsmentioning
confidence: 99%
“…In case of cabled distribution, the line impedance is mostly resistive and solution (11) is no longer applicable. An alternative solution can be found by observing that an active node like node B in Fig.2 I & takes the optimum value (7.b).…”
Section: Current-based Plug and Play Controlmentioning
confidence: 99%
“…In this case, equation (11) can be implemented in the EPP digital controller. A current limit is also set, to keep the actual currents within the converter capability.…”
Section: Voltage-based Plug and Play Controlmentioning
confidence: 99%
See 1 more Smart Citation